1997
DOI: 10.1063/1.364624
|View full text |Cite
|
Sign up to set email alerts
|

SmCo based sputtered films with CaCu5 and TbCu7 structures

Abstract: SmCo based films containing 20 at. % Fe and with Sm varying from 15.5 to 17 at. % have been synthesized to show the transition from ordered CaCu5 to disordered TbCu7 phase. For either phase, the demagnetization energy present during deposition can result in films with the crystallite c axes randomly splayed onto the film plane. It has been possible to synthesize the high anisotropy CaCu5 phase with either a (200) or (110) texture by adjusting the sputtering parameters to correspond to either a relatively high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…From 1990s, it has been found that the Cr underlayer can induce large in-plane coercivity in SmCo films [16][17][18][19][20][21][22][23]. Moreover, high temperature post-annealing and substrate heating have been found to be useful for enhancement of coercivity in SmCo films due to better crystallization of SmCo phases [21,24,25]. High in-plane coercivity has been reported in SmCo 5 thin films on MgO (1 0 0) substrates with a Cr underlayer [5,7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…From 1990s, it has been found that the Cr underlayer can induce large in-plane coercivity in SmCo films [16][17][18][19][20][21][22][23]. Moreover, high temperature post-annealing and substrate heating have been found to be useful for enhancement of coercivity in SmCo films due to better crystallization of SmCo phases [21,24,25]. High in-plane coercivity has been reported in SmCo 5 thin films on MgO (1 0 0) substrates with a Cr underlayer [5,7].…”
Section: Introductionmentioning
confidence: 94%
“…It has been found that appropriate single crystal substrates such as MgO (1 0 0), MgO (11 0) [4][5][6][7][8] and Si (1 0 0) [9][10][11][12] can lead to epitaxial or highly textured growth of SmCo 5 films with high coercivity values. On the other hand, for practical reason, many researchers have dedicated themselves to develop techniques for high coercivity SmCo 5 films grown on amorphous or polycrystalline substrates such as glass, Al and Al 2 O 3 [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In the early 1980s, amorphous SmCo films with small in-plane intrinsic coercivity (o3 kOe) were obtained by direct deposition on glass substrates [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Today thin SmCo films are of certain interest for applications in microelectromechanical devices (MEMs) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The SmCo 5 alloy, a representative permanent magnet material, is a promising candidate for the materials because of its extremely high uniaxial magnetocrystalline anisotropy, whose K u value is 1.1×10 8 erg/cm 3 or greater in the form of bulk alloy [34]. However, an SmCo 5 thin film exhibiting distinct perpendicular magnetic anisotropy had not been prepared, although the film with in-plane anisotropy is relatively easy to prepare, for instance, by using a Cr underlayer [35][36][37][38][39]. Recently, we succeeded in developing sputter-deposited SmCo 5 thin films with very high perpendicular magnetic anisotropy [40][41][42][43][44][45]; it will be stated in detail in this section.…”
Section: Development Of Permanent Magnet Thin Films With Very High Pementioning
confidence: 98%